Ameloblastic carcinoma: Presentation of a rare case - Palak H Shah; Rashmi Venkatesh; Chandramani B More; Vassandacoumara Vaishnavee (Wolters Kluwer Medknow Publications, 2017)
Ameloblastic carcinoma is a rare malignant tumor of odontogenic origin. It is an aggressive neoplasm that is locally invasive and can spread to regional lymph nodes or distant sites such as lung and bones. Histopathology is a vital tool for diagnosis of ameloblastic carcinoma and is also required to differentiate it from ameloblastoma. Its biologic behavior recommends necessity of early diagnosis and prompt treatment. However, due to lack of case reports with long-term follow-up, there is no established treatment protocol for these cases. Here, we are presenting a unique case of ameloblastic carcinoma of left mandible in a 48-year-old female patient treated successfully with resection and reconstruction by fibular graft.